Amphibian diversity conservation in a changing world: a view from Mexico - Ochoa Ochoa, L (2012)
Amphibians are the most abundant terrestrial vertebrates on Earth. They are crucial in maintaining the transfer of energy and matter from freshwater to terrestrial systems and are also indicators of ecosystem health. Mexico hosts great amphibian diversity with high levels of endemism. Nevertheless, the knowledge of amphibian ecology in the country is at an early stage. This thesis aspires to contribute to the knowledge of Mexican amphibian ecology and to the understanding of the processes underlying amphibian responses to environmental changes. To do so the thesis includes: 1) analyses from fine scales (at landscape level) based on data from two consecutive rainy seasons of fieldwork (nocturnal sampling), in two protected areas in southern Mexico, La Pera and Nahá; 2) at regional scales, analyses based on spatial databases of conservation instruments (i.e. environmental services, governmental, private, and community protected areas, etc.) generated specifically for Mexico; 3) to coarse scales (the whole country), analyses based on ecological niche modelling using the most complete database for Mexican amphibian records and climate layers developed purposely for the country. Thus, the thesis involves different time-scale processes, from ecological to biogeographical. In addition this thesis contains an analysis of the media representation of amphibian biodiversity threats and issues, specifically climate change, based on literature research. I was involved in the process of generating most of the databases used in this thesis. Whilst the main theme of this thesis is amphibian conservation, it also encompasses a wide range of specific subjects. Firstly, foundational knowledge about amphibian conservation is established in Chapter I. Also, the region, Chiapas in southern Mexico, where the fieldwork was carried out for two consecutive years (2009-2010) is described within a historical context and a glossary of terms is presented. In Chapter II, based on one year of fieldwork in two fragmented protected areas (PAs) of different management category, one state and one biosphere reserve, I examine how community structure is related to key features of the environment. The possible effects of governance issues in protected areas and their relationship with the drivers of amphibian metacommunities are also explored. A total of 144 transects were sampled from 33 patches in La Pera and 140 transects from 36 patches in Nahá. In each transect environmental variables were recorded. Partial Canonical Correspondence Analyses (partial CCA) indicated that the drivers of metacommunity patterns vary between the sampled landscapes. Habitat structure explained more of the community variation than either space or weather conditions: > 50% for La Pera and 30% Nahá; but the relationship to geographical space and local climate varied greatly. The differences in relationships among the environmental variables and between them and the amphibian metacommunities finds expression also in the pattern of human exploitation of these areas, which has latterly at least also found expression through differing governance. In Chapter III, the effects of environmental variation on metacommunities structure are explored. Metacommunity theory assumes that emergent properties can be determined that characterise a set of linked communities within a landscape. It follows that change in environmental conditions should generate changes in the metacommunity structure. In La Pera a total of 30 patches were sampled, with a total of 120 transects in 2009, and 133 transects in 2010. In Nahá 31 patches were sampled, with a total of 111 transects in 2009 and 122 transects in 2010. In the analyses of this chapter only transects sampled in both years are included. The total number of individuals increased greatly from 2009 to 2010, but the most abundant species between surveyed years varied slightly, in both areas. In La Pera metacommunity the structure changed from quasi-Clementsian to quasi-Gleasonian, while in Nahá it changed from Clementsian to Gleasonian. CCA show that the variance explained between years was similar. Re-arrangements in the metacommunity structures linked to environmental changes are observed. Results show that amphibian metacommunity structure can change with short environmental changes or disturbances, mainly weather variations from one year to another. This would suggest that metacommunity structures are a dynamic property in fluctuating systems. The aim of Chapter IV is to assess patterns of beta diversity for Mexican terrestrial vertebrates, and explore their relationships with environmental heterogeneity metrics at different spatial scales, identifying the most important surrogates at each spatial scale. The analyses in this chapter are based on the most complete database of Mexican terrestrial vertebrates, comprising distribution maps of 2513 species: 883 resident birds, 344 mammals, 364 amphibians and 811 reptiles. Higher β-diversity values are found along mountain ranges for amphibians, reptiles and mammals, whereas for birds high values are also found on the Mexican Plateau. Results demonstrate that the relationships between β-diversity and the environmental heterogeneity surrogates vary in form and strength across scale and between vertebrate groups. In Chapter V, I set out to characterize at fine scale, alpha and beta diversity patterns for Mexican amphibians and analyze how these patterns might change under a moderate climate-change scenario, and to highlight the overall consequences for amphibian diversity at the country level. The analyses are performed with a climatic envelope modelling approach using MaxEnt and a set of climatic layers developed specifically for Mexico. Models of future scenarios for Mexican amphibian alpha and beta diversity for 2020, 2050, 2080, show that high levels of species extinctions follow if low dispersal capability and high presence thresholds are used, but the overall geographic pattern of beta diversity remains stable. Zones of high beta diversity are associated with topographic formations, whilst the values of beta diversity initially increase, then decline over time under a moderate climate scenario. Extinctions (complete loss of range within country boundaries) are particularly intense during the period 2020–2050. The results imply that heterogeneous zones associated with mountain ranges will remain particularly important for amphibian diversity and thus such areas should be targeted for continued conservation prioritization in the face of climate change scenario. There is an inevitable degree of uncertainty associated with future climate projections and the possible ecological and biogeographical responses. Nevertheless, the climate change projections are typically translated in the media as certain. Chapter VI illustrates the interplay of these competing communication goals, through a review of the representations of the golden toad (Incilius [Bufo] periglenes) in print media and in peer-reviewed literature. The concept of “distanciation”, which means placing a distance between two connected issues (cause and effect), is introduced in this chapter, along with the potential issues that this process may generate in the implementation of conservation strategies. Distanciation is a perception created in the members of the audience of the media, but does not imply a total separation regarding an issue. For example, the audience is interested in the news about climate change effects, but they feel distant because the effects of climate change might be evident within a large time period (i.e. 2050); and although the causes are occurring now, the audience does not see the urgent need to act. Chapter VII represents the first attempt to analyze the status of conservation of some microendemic amphibians in Latin America when some social initiatives (e.g. private and community reserves) are included in the assessment. The efficiency of the existing set of governmental protected areas (PA), and the contribution of social initiatives for land protection of amphibians are evaluated. The chapter shows how the role of land conservation, through social initiatives, is fast becoming a crucial element for the survival of a substantial number of species not protected by state-designated PA. Given the current speed of land use change, we cannot expect to save all species from extinction, and so it must be decided, rather quickly, how to focus the limited resources available to prevent the greatest number of extinctions. In Chapter VIII, a simple conservation triage method is proposed. Using this triage method, the threat status for 145 micro-endemic Mexican amphibian species is evaluated, alongside potential threat abatement responses derived from existing policy instruments and social initiatives. Both indicators are combined to provide broad-scale conservation strategies that would best suit amphibian micro-endemic buffered areas (AMBAs) in Mexico. Results show that almost 25% of the species analysed urgently need field-base verification to confirm their persistence; for the rest, a conservation strategy is developed based on existing conservation instruments. Monitoring populations is essential in order to understand temporal patterns of community change and to better comprehend the underlying processes that shape and maintain biodiversity. These aspects, along with a general discussion focused mainly on the distanciation problem are addressed in Chapter IX.